Advance Selling in a Supply Chain Under Uncertain Supply and Demand - Cho, Soo-Haeng; Tang, Christopher S. (Manufacturing and Service Operations Management, 2013)
We examine three selling strategies of a manufacturer who produces and sells a seasonal product to a retailer under uncertain supply and demand: (1) advance selling—presells the product before observing uncertain supply and demand; (2) regular selling—sells the product after supply and demand are realized; and (3) dynamic selling—combines both advance and regular selling strategies. We model the first two strategies as single-period Stackelberg games, and we model the last strategy as a two-period dynamic Stackelberg game. By comparing the equilibria of these games, we formalize our understanding of several intuitive results. For example, from the manufacturer's perspective, dynamic selling dominates advance selling and regular selling: having more selling opportunities is beneficial to the manufacturer. However, from the retailer's perspective, we find two counterintuitive results: (a) postponing the ordering decision can be detrimental—the retailer can be worse off under regular selling than under advance selling; and (b) more ordering opportunities can be detrimental—the retailer can be worse off under dynamic selling than under advance selling. In addition, we analyze the impact of supply and demand uncertainties under these strategies and find that both types of uncertainties can be beneficial to the retailer.